2013
DOI: 10.1007/s00405-013-2350-2
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in a child with posttraumatic single-sided deafness

Abstract: Cochlear implantation has become a standard therapy for children with bilateral profound hearing loss, resulting in substantial and sustainable benefits for the development of expressive and receptive and expressive language skills and cognition. During the last few years, audiologic and otologic criteria for cochlear implantation have been expanded. Recently, patients with profound single-sided deafness with or without tinnitus have received cochlear implants despite normal to near-normal hearing on the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
2
30
0
2
Order By: Relevance
“…Results from CI surgery in young children with acquired SSD suggest results comparable to those of adults suffering from acquired SSD [Cadieux et al, 2013;Hassepass et al, 2013;Plontke et al, 2013;Tzifa and Hanvey, 2013;Távora-Vieirea and Rajan, 2015]. Evidence of rehabilitation of binaural hearing skills in quiet and noise as well as improvement in the localisation of sounds has been demonstrated.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Results from CI surgery in young children with acquired SSD suggest results comparable to those of adults suffering from acquired SSD [Cadieux et al, 2013;Hassepass et al, 2013;Plontke et al, 2013;Tzifa and Hanvey, 2013;Távora-Vieirea and Rajan, 2015]. Evidence of rehabilitation of binaural hearing skills in quiet and noise as well as improvement in the localisation of sounds has been demonstrated.…”
Section: Introductionmentioning
confidence: 81%
“…Evidence of rehabilitation of binaural hearing skills in quiet and noise as well as improvement in the localisation of sounds has been demonstrated. Moreover, CI surgery remains the only treatment option available to individuals with SSD that may enable children to regain or improve binaural hearing [Arndt et al, 2011b;Cadieux et al, 2013;Gordon et al, 2013;Plontke et al, 2013;Tzifa and Hanvey, 2013]. Hassepass et al [2013] reported improvements in speech comprehension in noise and localisation of sound following CI surgery in 3 children with unilateral hearing loss (UHL).…”
Section: Introductionmentioning
confidence: 99%
“…Su repercusión durante la edad infantil es aún mayor, por su alta incidencia 25 y por su implicación directa en el desarrollo auditivo, rendimiento académico y en la autoestima de estos niños 26 . En los niños con sordera unilateral se están realizando estudios para demostrar la eficacia que supondría la implantación coclear, tanto a nivel de integración auditiva como derivados del beneficio binaural [27][28][29] . Más allá de los beneficios clínicos mencionados, una de las principales razones para promover la implantación coclear en niños con sordera unilateral es facilitar un completo desarrollo del sistema auditivo central dentro del periodo crítico o de mayor sensibilidad que se corresponde con los primeros años de la vida.…”
Section: Implante Coclear En Sordera Unilateralunclassified
“…Localization deviation from the source decreased in both of the two subjects who were tested. In noisy conditions, Plontke et al reported improvements in angle detection error when the noise was presented frontally or to the CI side [36]. Finally, Cadieux et al demonstrate that for 3/5 children implanted with asymmetric hearing loss, adding a contralateral hearing aid significantly increased hearing ability compared to the CI-alone or HAalone conditions [37].…”
Section: Sound Localization Benefits After Unilateral Cochlear Implanmentioning
confidence: 99%
“…Plontke et al present a case where a child with a lateral skull base fracture and imminent fibrosis was implanted [36]. Improvements in speech discrimination in both quiet and noise, localization, and patient satisfaction .…”
Section: Speech Benefits After Unilateral Cochlear Implantationmentioning
confidence: 99%